Ultra-sensitive H2S sensors based on hydrothermal/impregnation-made Ru-functionalized WO3nanorods - Viruntachar Kruefu (2018)
© 2015 Elsevier B.V. All rights reserved. Ultra-sensitive H2S gas sensors based on the hydrothermal/impregnation-synthesized WO3one-dimensional (1D) nanostructures functionalized with Ru are presented. The particle properties were characterized by XRD, BET, SEM, TEM and EDS analyses. The H2S-sensing performances in terms of sensor response, response/recovery times and selectivity were optimized by varying Ru concentration. The optimal sensing film (0.50 wt% Ru-WO3) showed an ultra-high sensor response of ∼192 and short response time of ∼0.8 s to 10 ppm of H2S at 350 C. In addition, 0.50 wt% Ru-WO3nanorods (NRs) exhibited much higher H2S selectivity against NO2, SO2, C2H5OH and NH3compared with unloaded WO3NRs. Furthermore, the catalyst selectivity of Ru toward H2S was found to be significantly higher than those of three other metals including Ni, Nb and Au, respectively. Therefore, 0.50 wt% Ru-WO3sensor is one of the most promising candidates for highly sensitive and selective detection of H2S.